Analysis of bone healing with a novel bone wax substitute compared with bone wax in a porcine bone defect model. (26th July 2018) - Tham, Tristan; Roberts, Keith; Shanahan, John; Burban, John; Costantino, Peter
Aim: This pilot study describes a novel composite of hydroxyapatite and biodegradable polylactic acid with wax-like handling properties (BoneSeal ® ). The goal was to compare quantitative measures of bone healing between BoneSeal versus Bone wax.Materials & methods: BoneSeal and Bone wax were introduced into separate defects of a single porcine specimen. After 6 weeks, the defect sites were harvested for analysis.Results: Both groups had similar hemostatic action. The amount of new bone was significantly greater at 6 weeks in the BoneSeal group (38.05%) versus the Bone wax group (11.88%), p = 0.028.Conclusion: In this pilot study, BoneSeal had higher amounts of new bone formation compared with Bone wax. Lay abstract: This small pilot study compares two materials, Bone wax and BoneSeal, which could be used in bone surgery. In bone surgery, there is a need for the materials to stop bleeding as well as have good bone healing capabilities. We investigated the bone healing characteristics of two different materials. We implanted these materials into the arm and leg bones of a single pig. After a period of 6 weeks, we investigated the sites of implantation. We found that implantation sites of BoneSeal had higher amounts of new bone formation.